Geographic and Breed Distribution Patterns of an A/G Polymorphism resent in the Mx Gene Suggests Balanced Selection in Village Chickens - Ommeh, S.; Jin, L.N.; Eding, H.; Muchadeyi, F.C.; Sulandari, S.; Zein, M.S.A.; Danbaro, G.; Wani, C.E.; Zhao, S.G.; Nie, Q.H.; Zhang, X.Q.; Ndila, M.; et al. (International Journal of Poultry Science, 2009)
An A/G Single Nucleotide Polymorphism (SNP) at position 1,892 of the Mx gene coding sequence has been linked to susceptibility/resistance to avian viral infection in vitro. Using PCR-RFLP and sequencing methods, 1,946 samples from 109 populations from Asia, Africa and Europe; grouped as indigenous village, commercial, fancy chicken as well as wild junglefowl were genotyped for the polymorphism. Allele and genotype frequencies were calculated. Only the G allele was present in Ceylon junglefowl Gallus lafayetti. Using the wild red junglefowl G. gallus population as reference, we assessed if the A/G alleles and genotypes frequencies have been affected by the breeding history and the geographic dispersion of domestic chicken. Within group variation was high but overall there were no significant variation in distribution of alleles and genotypes frequencies between the red junglefowl and indigenous village chickens (p>0.1946), with the exception of the East Asian group (p